(untitled) (World Science, 2020)
The article presents the results of studies of histological changes in the skin of rats in different periods after burn injury (1, 3, 7, 14, 21 and 30 days) with an area of 21-23 % of the body surface of II-III degree on the background of intravenous injection of the first 7 days of HAES- LX-5 % solution at a dose of 10 ml/kg. From the 1st to the 3rd day of the experiment, it was found that the condition of the structural components of the skin was close to that of animals treated with an intravenous first 7 days of 0.9 % NaCL solution. The positive effect of HAES-LX-5 % corrective solution infusion was observed from day 7 of the study. It is revealed that the drug significantly reduces dystrophic and necrobiotic processes in the epidermis, stimulates neoangiogenesis, has an antiswelling and protective effect on the endothelium of the blood vessels.